Psychotherapeutic prevention of drug and mental disorders in military personnel during emergency situations - Evgenii Yu. Sokolov (Clinical Medicine (Russian Journal), 2026)
Article is devoted to due use of psychotherapeutic methods of prevention and treatment of the post-traumatic stress disorder (PTSD), personal, including, narcological and other mental deviations at experts of dangerous, extreme professions during their work in extraordinary conditions. Special attention is paid to mandatory training of military personnel in self-regulation methods in order to prevent PTSD after completing tasks in a combat situation.